2016
DOI: 10.2147/ndt.s109414
|View full text |Cite
|
Sign up to set email alerts
|

Association between sequence variations of the Mediterranean fever gene and the risk of migraine: a case–control study

Abstract: Migraine pathogenesis involves a complex interaction between hormones, neurotransmitters, and inflammatory pathways, which also influence the migraine phenotype. The Mediterranean fever gene (MEFV) encodes the pyrin protein. The major role of pyrin appears to be in the regulation of inflammation activity and the processing of the cytokine pro-interleukin-1β, and this cytokine plays a part in migraine pathogenesis. This study included 220 migraine patients and 228 healthy controls. Eight common missense mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Headache is the most common neurological manifestation in the IL-1β-mediated autoinflammatory disorders. This is consistent with the emerging role for inflammasomes in migraine ( 92 ) and the association of MEFV variants with the risk of migraine ( 93 ). Moreover, seizures is another commonly reported neurological manifestation of these diseases.…”
Section: Autoinflammatory Disorderssupporting
confidence: 86%
“…Headache is the most common neurological manifestation in the IL-1β-mediated autoinflammatory disorders. This is consistent with the emerging role for inflammasomes in migraine ( 92 ) and the association of MEFV variants with the risk of migraine ( 93 ). Moreover, seizures is another commonly reported neurological manifestation of these diseases.…”
Section: Autoinflammatory Disorderssupporting
confidence: 86%
“…In a study by Coşkun et al [13], 220 patients with FMF were compared with a group of 228 healthy people as a control group. Five mutations of M694V, M694I, M680I, V726A, R761H, and E148Q were determined.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that biallelic mutations in MEFV gene were correlated with an increased risk of migraine in the Turkish population. Furthermore, MEFV mutations appeared to be related to a higher frequency and shorter durations of migraine attacks [ 61 ].…”
Section: Genetic Findings Related To the Immune System In Migraineursmentioning
confidence: 99%